Fatty acid‐binding protein 3 regulates differentiation of IgM‐producing plasma cells. (14th July 2020) - Kobayashi, Shuhei; Phung, Hai The; Tayama, Shunichi; Kagawa, Yoshiteru; Miyazaki, Hirofumi; Yamamoto, Yui; Maruyama, Takashi; Ishii, Naoto; Owada, Yuji
Abstract : Plasma cells (PCs), which aim to protect host health, produce various subsets of immunoglobulin (Ig) in response to extracellular pathogens. Blimp‐1 (encoded by Prdm1 )—a protein that is highly expressed by PCs—is important for PC functions, including the generation of Igs. Fatty acid‐binding protein 3 (FABP3) is a carrier protein of polyunsaturated fatty acids (PUFAs) and participates in multiple cellular functions. Although the functions of FABP3 in neurons and cardiac myocytes are well‐noted, their roles in immune cells remain to be fully elucidated. In this study, we demonstrate that FABP3 is expressed in activated B cells and that FABP3 promotes PC development and IgM secretion. Moreover, we provide the first evidence that FABP3 is necessary for Blimp‐1 expression, by regulating the histone modification of its promoter region. Taken together, our findings reveal that FABP3 acts as a positive regulator of B‐cell activation by controlling histone acetylation of the Blimp‐1 gene, thereby playing a role in host defense against pathogens. Abstract : Humoral (antibody‐mediated immunity) plays a key role in protecting hosts from pathogens. Dietary intake of fatty acids has been shown to influence inflammation, fueling interest in understanding the impact of lipid metabolism in B cell function. Fatty acid‐binding protein 3 (FABP3) transports long‐chained fatty acids and participates in multiple cellular functions. Here, Kobayashi et al show that FABP3, whose expression is increased upon B‐cell activation, controls histone acetylation of the Blimp‐1 gene ( Prdm1 ), a master regulator of the development and function of antibody‐secreting plasma cells. This leads to enhanced IgM secretion and differentiation of plasma cells.